A survey of awareness, opinion and reported use of clinical practice guidelines (CPG) of the Royal College of Anesthesiologists of Thailand - Siriporn Pitimana-aree (2018)
Background: Up to the present (2006), The Royal College of Anesthesiologists of Thailand (RCAT) has proposed and revised six practice guidelines. For guidelines to achieve their objectives, anyone who gets involved needs to be aware of the guidelines, be able to accept, and adhere to them. Although the authors did introduce their guidelines by several passive means, the authors have not yet ascertained what the result were. Objective: The primary objective of the present study was to assess awareness, opinion, limitation, and reported use of guidelines. The secondary objective was to identify factors associated with variation, agreement, and reported use of guidelines. Material and Method: A cross sectional, self-report survey study was conducted. An anonymous questionnaire including prepaid-addressed reply envelopes was mailed to 600 anesthesiologists and 1,300 nurse anesthetists, nationwide, based on the college's list. The questions covered respondents' general characteristics: awareness, agreement, and reported use of the existing guidelines; opinion on implementation media, which guidelines the members need, their local guidelines, and the impact of guidelines on their practice. All data were extracted and reported using descriptive statistics. Multiple logistic regression was done to identify factors associated with an agreement with and a reported use of the guidelines. Results: The overall response rate was 33.4% and nurse anesthetists had a higher response than anesthesiologists. Forty-six percent of the respondents were aware of the existing guidelines. This result corresponded to percentage of those who had read the guidelines (41%). Among the six existing guidelines, the least two guidelines reported use of and agreement with, were those for labor analgesia and conscious sedation (23-28%; 24-28%). The guidelines for spinal anesthesia received the most response (46%). For respondents who had read the guidelines, most of them (80% to 94%) rated the level of agreement and reported use as good to excellent. The respondents also rated the announcement of the guidelines during the annual meeting of the Royal College of Anesthesiologists of Thailand as the best implementation strategy. Impracticability, inadequate dissemination, and un-cooperation among colleagues were the three most important obstacles of using the guidelines. In addition, the present study demonstrated three significant factors, anesthesiologists, regional hospitals, and general hospitals, as associated with reporting frequent use of and high agreement with the guidelines. Conclusion: The low level of awareness and reported use of the present guidelines among the members reflects poor implementation and dissemination. However, the present study reveals some information that will guide the authors to introduce intensive and targeted interventions to encourage the members to comply and adhere to the guidelines designed to improve the quality of patients' care.